Vacuum-assisted staged omphalocele reduction: A preliminary report - Nissen, Matthias; Romanova, Anna; Weigl, Elena; Petrikowski, Laura; Alrefai, Mohamad; Hubertus, Jochen (Frontiers in Pediatrics, 2022)
Introduction: Omphalocele represents a rare congenital abdominal wall defect. Due to the viscero-abdominal disproportion, in giant omphalocele, gradual reintegration of eviscerated organs is often associated with medical challenges. We report our preliminary experience combining staged gravitational reduction with vacuum (VAC) therapy as a novel approach for treatment of giant omphalocele. Patients and methods: Retrospective chart review of six patients (five females) born between 09/2018 and 05/2022 who underwent staged reduction of giant omphalocele in conjunction with VAC therapy. Treatment was performed at two German third level Pediatric Surgery Departments. Biometric and periprocedural data was assessed. Main outcome measure was the feasibility of VAC therapy for giant omphalocele. Data is reported as median and interquartile range (Q1-Q3). Results: Gestational age was 37 (37-38) weeks, birth weight was 2700 (2500-3000) g. VAC-dressing was changed every 3 (3-4) days until abdominal fascia closure at the age of 9 (3-13) days. Time to first/ full oral feeds was 3 (1-5)/ 20 (12-24) days with hospital stay of 22 (17-30) days. Follow-up was 8 (5-22) months and complications were of minor extent (none: n=2; Clavien-Dindo I: n=3; Clavien-Dindo II: n=1), comprising a delayed neo-umbilical cord rest separation (n=2) and/or concomitant neo-umbilical site infection (n=2) with no redo surgery. Conclusion: In neonates with giant omphalocele, VAC constitutes a promising and technically feasible enhancement of the staged gravitational reduction method. This study shows evidence that VAC may accelerate restoration of the abdominal wall integrity in giant omphalocele, thus minimizing associated comorbidities inherent to a prolonged hospitalization.